Clinical and bacteriological characteristics of invasive pneumococcal disease after pneumococcal 10-valent conjugate vaccine implementation in Salvador, Brazil - Leite,Carolina Regis (2016)
Abstract Invasive pneumococcal disease is a relevant public health problem in Brazil, especially among children and the elderly. In July/2010 a 10-valent pneumococcal conjugate vaccine was introduced to the immunization schedule of Brazilian children under two years of age. Between July/2010 and December/2013 we conducted a case-series study on invasive pneumococcal disease in Salvador, Brazil to describe the clinical and bacteriological profile of invasive pneumococcal disease cases during the post-implementation period. Eighty-two cases were eligible. Mean age was 31 years (interquartile range, 3–42); 17.1% and 30.5% were under 2 years and 5 years, respectively. Pneumococcal meningitis (n = 64, 78.1%), bacteraemic pneumococcal pneumonia (n = 12, 14.6%) and bacteraemia (n = 6, 7.3%) were the clinical syndromes identified. Thirty-three different serotypes were found. Of these, serotype 14 (n = 12, 14.6%) was the most common, followed by 23F (n = 10, 12.2%), 12F (n = 8, 9.8%), 18 C (n = 5, 6.1%) and 6B (n = 5, 6.1%). Investigations conducted in Salvador in the pre-vaccine period did not identify serotype 12F as one of the most prevalent serotypes. Increase of serotype 12F was observed in different regions of Brazil, in the post-vaccine period. Among children under two years of age, the target group for 10-valent pneumococcal conjugate vaccine, 11 (78.6%) of the 14 isolated strains of Streptococcus pneumoniae belonged to vaccine serotypes; at least 50% of these children were not vaccinated. The relatively recent implementation of 10-valent pneumococcal conjugate vaccine in Brazil reinforces the need to maintain an active surveillance of invasive pneumococcal disease cases, considering the possible increase of invasive pneumococcal disease cases related to non-vaccine serotypes and the changes on the clinical presentation of the disease.